ДИСТРИБЬЮТОРСКИЙ ДОГОВОР В ПРАВЕ ЗАРУБЕЖНЫХ СТРАН - Сосна, Александр, Арсени Игорь (SUPREMANCE OF LAW, 2016)
In this article, the author investigated and analyzed the legal regulation peculiarities and distribution agreement places the right of foreign countries. In particular, the main problems arising from the legal regulation in the legislation of certain foreign countries, as well as the possibilities of the implementation of certain provisions of foreign law in the legal system of the Republic of Moldova in order to regulate the distribution agreement.